Guidelines for learning and innovation skills development of Silpakorn university’s student follow Thailand 4.0 policy. - Jamduang, Thanakitt (Journal of Management Science Nakhon Pathom Rajabhat University, 2019)
The objectives of the research are 1) to study the level of the learning and innovation skills 2) to compare the level of the learning and innovation skills consolidated by personal factors 3) to study the factors that affect the learning and innovation skills 4) to study the developmental guideline of the learning and innovation skills of the students of Silpakorn University according to Thailand 4.0 national policy. The sample is the fourth year of undergraduate students of the year 2560 of Silpakorn University in the total of 350 students, using random class and simple random as the sampling methods, and 5 in-depth interview participants. The research tools consist of the questionnaire and guided questions for the in-depth interview. The researcher analyzed data using the distribution of Frequency, Percentage, Arithmetic Mean, Standard Deviation, Independent Samples t-test, One-way ANOVA, and content analysis. The research found that 1) the overall level of the learning and innovation skills of the students of Silpakorn University according to Thailand 4.0 national policy are ranked in high level 2) when comparing the learning and innovation skills of the students of Silpakorn University according to Thailand 4.0 national policy consolidated by personal factors found that only sex and cumulative grade point averages affect the learning and innovation skills of the students of Silpakorn University according to Thailand 4.0 national policy statistically significant at 0.05 3) Educational standards Curriculum and teaching methods affect learning and innovation skills. According to the policy of Thailand 4.0 at the significance level of 0.05 and can predict the learning and innovation skills of 33 percent, respectively 4) The development of learning and creative skills of Silpakorn University students according to the country policy 4.0 (4.1) Educational standards should be adjusted to meet the needs of the learners. Focus on teaching and learning by integrating knowledge and action. (4.2) Skill assessment there should be a variety of assessments. Focus on the evaluation of student work that has been created. (4.3) Curriculum and teaching methods There should be a change in teaching methods using the Project Based Teaching Methodology in order to create students' creativity and learning process. (4.4) Professional Development It should be developed in terms of understanding the direction of student skills development to keep up with the modern age. (4.5) Learning environment the classroom environment should be improved to suit the learning needs. Article history : Received 2 May 2018 Revised 2 August 2018 Accepted 10 August 2018 SIMILARITY INDEX = 0.00